167 Production performance and egg quality of free-range laying hens fed diets containing chopped full-fat dried black soldier fly larvae. (7th December 2018) - Bejaei, M; Cheng, K
Abstract: A 14-week long feeding trial was carried out to evaluate the efficiency, safety and effects on egg quality of three experimental diets using 0%, 10% and 18% chopped full-fat dried black soldier fly larvae (DBSFL) to partially or fully replace soybean meal in free range layer diets. The feed was provided in mash form and DBSFL was mechanically chopped (3 – 5 mm) before mixing in the diet. For each of the three diets, 30 pullets were housed in 2 mobile poultry trailers. The weight gain, feed intake, egg production, egg weight, feed conversion ratio, health and welfare parameters, blood biochemistry and hematology, excreta microbiology, digestive tract mass, egg shell weight and thickness, interior egg quality (albumen weight and height, yolk weight and color, and Haugh Units), yolk metal and fatty acid compositions, and sensory evaluation were examined. Data were analyzed by Least Squares ANOVA with repeated measures using JMP®. Results of the study indicated that control hens had significantly better egg production and feed conversion ratio than 18% DBSFL hens probably because of the higher fat content, presence of chitin and bulkiness of the 18% feed. Control hens had better weight gain, and heavier shell and albumen weights than DBSFL eggs. 18% DBSFL hens had lower plasma albumin, total protein and triglycerides, but heavier duodenum weights than the control hens. Despite these apparent short-comings, the 18% hens were still gaining weight during the laying period, maintaining above 90% hen-day egg production, and their eggs were still in the "Large" egg category. There were no obvious differences between the three treatment groups in yolk metal content or sensory characteristics. In conclusion, if the digestibility of DBSFL can be improved, it may fully replace soybean meal in laying hen diets.